2020
DOI: 10.2494/photopolymer.32.805
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Property of Tellurium-Containing Molecular Resist Materials for Extreme Ultraviolet Lithography System

Abstract: We examined the synthesis and resist properties of tellurium-containing molecular resist materials. By the condensation reaction of anisol, phenol, and 2-phenylphenol with tellurium tetrachloride (TeCl 4), dichloro di(4-hydroxyphenyl) telluride (CHPT), dichloro di(4-hydroxy-3-phenylbenz) telluride (CHBT), di(4-hydroxyphenyl) telluride (HPT), and di(4-hydoxy-3-phenylbenz) telluride (HBT) were synthesized. These were reacted with 2methyl-2-adamantyl bromo acetate, yielding corresponding compounds CHPT-AD, CHBT-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…However, a good sensitivity curve could not be obtained in the case of TDP-BEPMSion. Presumably because of that transparency of TDP-BEPMSion might be low due to tellurium, which has high EUV absorption efficiency 14,15 .…”
Section: Resist Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, a good sensitivity curve could not be obtained in the case of TDP-BEPMSion. Presumably because of that transparency of TDP-BEPMSion might be low due to tellurium, which has high EUV absorption efficiency 14,15 .…”
Section: Resist Sensitivitymentioning
confidence: 99%
“…For example, Ueda et al synthesized calix [4]resorcinarene with pendant t-butyloxycarbonyl group as a molecular resist and it's a thin film could offer a resist pattern with 1.5 μm L/S using UV exposure tool [3]. Our research group has also reported the development of molecular resist materials based on ladder cyclic oligomer noria ("noria" = water wheel in Latin) [4 -12], tannic acid derivative [13], and telluriumcontaining materials [14,15]. These molecular resists have been considered to achieve higher sensitivity, but their roughness of resist pattern could not improve.…”
Section: Introductionmentioning
confidence: 99%
“…In a next-generation resist process, the incorporation of elements with a large EUV absorption cross section into the resist formula will be required to suppress shot noise effects. Metal elements such as Ti, 7,8) Zr, 7,[9][10][11][12][13][14] Sn, [15][16][17][18][19] Sb, 20) Hf, 8,9,11) Bi, 21) and Te 22) have been examined as high-EUV absorption units.…”
Section: Introductionmentioning
confidence: 99%
“…At present time, a chemically amplified resist (CAR) system is utilized to increase sensitivity [8][9][10][11]. We have also reported the synthesis of the higher sensitive EUV resist materials based on ladder cyclic oligomer noria derivatives ("noria" = water wheel in Latin) [12][13][14][15][16][17][18][19][20], tannic acid derivatives [21], tellurium-containing compounds [22][23], cage oligomer consistent of calixarene in the main chain [24], botryosin-type polymer [25], and iodinecontaining hyper branched polymer [26]. Consequently, resist sensitivities were consistent with the structures of resist materials and these results prompt us the systematical examination of the relationship between the sensitivity and the structure of the resist materials.…”
Section: Introductionmentioning
confidence: 99%